Microstructural changes in the spinal cord of adults with cerebral palsy - TREVARROW, MICHAEL P (Dev Med Child Neurol, 2021)
AIM: To quantify the microstructural differences in the cervical-thoracic spinal cord of adults with cerebral palsy (CP). METHOD: Magnetic resonance imaging of the proximal spinal cord (C6–T3) was conducted on a cohort of adults with CP (n=13; mean age=31y 11mo, standard deviation [SD] 8y 7mo; range=20y 8mo–47y 6mo; eight females, five males) and population norm adult controls (n=16; mean age=31y 4mo, SD 9y 9mo; range=19y 4mo–49y 5mo; seven females, nine males). The cross-sectional area (CSA) of the spinal cord, gray and white matter, magnetization transfer ratio (MTR), and fractional anisotropy of the cuneatus and corticospinal tracts were calculated. RESULTS: The total spinal cord CSA and proportion of the spinal cord gray matter CSA were significantly decreased in the adults with CP. The corticospinal tracts’ MTR was lower in the adults with CP. Individuals that had reduced gray matter also tended to have reduced MTR in their corticospinal tracts (r=0.42, p=0.029) and worse hand dexterity clinical scores (r=0.53, p=0.004). INTERPRETATION: These results show that there are changes in the spinal cord microstructure of adults with CP. Ultimately, these microstructural changes play a role in the extent of the hand sensorimotor deficits seen in adults with CP.